FILANTROPI ISLAM DAN PEMBERDAYAAN EKONOMI - Saripudin, Udin (Universitas Islam Negeri Sunan Kudus, 2016)
Poverty is an interesting theme discussed especially among social scientists. Before getting to know scientific studies on the issue of poverty, the community has been running a tradition to respond to the problems of poverty in the form of giving. The